Kepemimpinan Kristen Transformatif Berbasis inklusif dan implikasinya bagi Lembaga Disabilitas Kristen di Indonesia - Carolina, Gressia; Romika, Romika; Rahayu, Esti (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to explore the application of inclusive-based transformative Christian leadership in supporting the empowerment of persons with disabilities in Christian disability institutions in Indonesia. This research employs a qualitative research method in the form of library research, which involves collecting, studying, and drawing conclusions from sources such as articles, journals, and books related to the discussed topic. The analysis indicates that inclusive-based transformative Christian leadership promotes a paradigm shift in the management of disability institutions. Leaders who apply the values of love, justice, and respect for diversity succeed in creating a collaborative environment that prioritizes the active participation of persons with disabilities in decision-making processes. Inclusive-based transformative Christian leadership not only addresses the needs of disability institutions but also reflects the Christian mission of serving with love, justice, and respect for all individuals